Decoupling of valence and coordination number contributions at perovskite surfaces - Tileli,V; Ahmad,E; Webster,R; Mallia,G; Duchamp,M; Stoerzinger,K; ShaoHorn,Y; DuninBorkowski,R; Harrison,N (2016)
Perovskite oxide nanostructures are on the forefront of technology due to the wide spectrum of possible applications pertinent to renewable energy sources, such as watersplitting, solar cells, fuel cells, batteries, and catalysis. In particular, the exceptional properties for the oxygen reduction reaction in catalysis have been detailed recently in a volcano plot and the results reveal that orthorhombic, JahnTeller distorted LaMnO 3 perovskite nanoparticles are the leading, nonnoble metal candidate for enhanced catalytic activity on the cathode electrode of fuel cells [1]. Since the functional properties of these nanoparticles lie on their active surfaces, our approach involves a detailed structural and chemical evaluation of the surfaces on the atomic scale to determine what/where the reaction centres are. Subsequently, the morphology of the particles can be optimised to maximise the number of these reaction centres, allowing us to attain the highest possible performance of perovskite catalysts. From structural transmission electron microscopy (TEM) data it was determined that polar facets exist on crystallites, which lead to assumptions on possible surface reconstruction/relaxation. However, high resolution TEM indicated that the atomic terminations of several surfaces remained defectfree up to the very surface with no visible reconstruction taking place [2], as shown in Figure 1. Next, the surface and subsurface of the working perovskite catalyst was probed by high spatial and temporal resolution electron energyloss spectroscopy (EELS) in scanning TEM mode. The results revealed that the surface shows different character than the bulk. Tan et al. has previously shown that different oxidation states of Mn can be probed at neighbouring sites in the same compound